Certainty of Determining Heirs of Different Religions And Implications In Preparing An Inheritance Certificate - Sevira Eka Nur Salsabila; Abdul Rachmad Budiono; Rachmi Sulistyarini (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
This study aims to analyze the legal certainty in determining heirs of different religions and its implications in the issuance of a Certificate of Inheritance (SKW) in the Indonesian legal system. The problem of interfaith inheritance creates a dilemma between the normative provisions of Islamic inheritance law that prohibit inheritance between parties of different religions and the demands of justice in a pluralistic society. Normatively, the Compilation of Islamic Law emphasizes that religious differences are a barrier to inheritance, so that non-Muslim heirs do not have the right to inherit from Muslim heirs. However, in judicial practice, the Supreme Court through its jurisprudence provides a solution through the mechanism of mandatory wills to bridge the tension between legal certainty and substantive justice. This study uses a normative juridical research method with a statutory regulatory approach and a case approach, particularly through an analysis of court decisions related to interfaith inheritance. The results of the study indicate that the certainty of determining heirs of different religions is not only determined by written legal norms, but also by the development of jurisprudence that provides legal protection for non-Muslim heirs through mandatory wills. The implications of issuing a SKW place notaries in a limited position, namely, merely formalizing legal facts based on court rulings and not having the authority to determine the status of heirs. Therefore, notaries are required to exercise prudence and ensure that every deed they create complies with applicable law to ensure its legal validity